2022
DOI: 10.3389/fpubh.2022.876966
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Cohort Study on the Adverse Effects Evaluation After Messenger RNA COVID-19 Vaccination Among Pregnant Healthcare Employees in Penang General Hospitals

Abstract: IntroductionThe year 2020 saw the emergence of novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which became a great threat to public health worldwide. The exponential spread of the disease with millions of lives lost worldwide saw the emergence of an accelerated vaccine development with emergency approval from well-known regulatory bodies such as the US Food and Drug Administration, followed by widespread vaccine deployment despite a paucity in safety profile data. This issue becomes even m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We included 16 studies (425 867 women) reporting SARS-CoV-2 infection-related outcomes6 7 17 19 21 31 33 36 38–45 and 35 (1 362 172 women) reporting pregnancy-related maternal and offspring outcomes in the secondary analysis 17 18 21–24 29–34 36 38 39 41–60. Twenty-three studies reported reactogenicity outcomes (94 206 women) following vaccination 38 39 46 61–80…”
Section: Resultsmentioning
confidence: 99%
“…We included 16 studies (425 867 women) reporting SARS-CoV-2 infection-related outcomes6 7 17 19 21 31 33 36 38–45 and 35 (1 362 172 women) reporting pregnancy-related maternal and offspring outcomes in the secondary analysis 17 18 21–24 29–34 36 38 39 41–60. Twenty-three studies reported reactogenicity outcomes (94 206 women) following vaccination 38 39 46 61–80…”
Section: Resultsmentioning
confidence: 99%
“…[157] We included 134 studies (87% RNA vaccines) published until December 31, 2022. We found more than 20 new studies that our present review evaluating the safety of COVID-19 vaccines during pregnancy [158] , [159] , [160] , [161] , [162] , [163] , [164] , [165] , [166] , [167] , [168] , [169] , [170] , [171] , [172] , [173] , [174] , [175] , [176] , [88] , [177] . Most of studies were conducted in Europe [159] , [160] , [162] , [169] , [170] , [171] , [177] , North America [163] , [168] , [172] , [173] , [175] , [88] and Asia [158] , [161] , [164] , [167] , [174] , [176] .…”
Section: Discussionmentioning
confidence: 99%
“…While safety concerns exist for COVID-19 vaccines due to their new technology and the initial exclusion of pregnant women from efficacy trials, emerging data offer reassuring insights into their safety. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%